Auf Augenhöhe mit Russland: Welche militärischen Ressourcen werden benötigt? - Richard Reichel (Wirtschaftsdienst, 2025)
– The reduction in defense spending, often referred to as the “peace dividend,” from 2.7 % to 2.8 % of Germany's GDP in the late 1980s to just 1.2 % of GDP by the end of the 2010s, has led to a near-complete loss of defense capability over more than 30 years. Given the current global political situation, there is no question that a massive increase in key weapons systems is necessary. The guideline should be a roughly equal level of spending between the three largest European NATO states combined and Russia. Along with the other European NATO states (Poland, the Baltic and Scandinavian states, and several other countries) this should act as sufficient deterrence.
Keywords: H56; H60; H41; 330; Militärausgaben; Militärforschung; Rüstungspolitik; NATO-Staaten; Russland; Militärausgaben; Militärforschung; Rüstungspolitik; NATO-Staaten; Russland